New type phase transitions in the Mitsui model with bimodal random ﬁeld - Stasyuk, I.V.; Velychko, O.V. (Condensed Matter Physics, 1999)
Thermodynamic functions of the Mitsui model with bimodal random ﬁeld
are calculated in the mean ﬁeld approximation for long–range interactions with an exact treatment of the intracell interaction of pseudospins.
Conditions of the appearing of the ﬁrst order phase transition between
nonequivalent nonpolar phases or the possibility of phase separation are
investigated. Термодинамічні функції моделі Міцуї в бімодальному випадковому
полі отримано в наближенні середнього поля для далекосяжних взаємодій при точному врахуванні взаємодії псевдоспінів у межах комірки. Вивчаються умови появи фазового переходу першого роду між
нееквівалентними неполярними фазами та явища фазового розшарування.